Magnetic Fe3O4/carbon sphere/cobalt composites for catalytic oxidation of phenol solutions with sulfate radicals - Wang, Yuxian; Sun, Hongqi; Ang, Ming; Tade, Moses; Wang, Shaobin (Elsevier BV, 2014)
Magnetic carbon nanospheres (Fe3O4/CS core/shell) and their supported Co3O4 nanoparticles were synthesized using a novel one-step hydrothermal method followed by heat treatment. The nanocomposites were characterized by powder X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDS), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), and N2 sorption isotherms. The catalytic properties of the nanocomposites in activating Oxone® for oxidation of phenol solution were investigated. Fe3O4/CS supported Co3O4 nanoparticles exhibited high activity in Oxone® activation for phenol degradation with 100% conversion within 30 min. Phenol degradation was found to follow the first order kinetics. The nanoparticles also displayed good water dispersion and magnetic separation under the magnetic field. The deactivationof catalysts was investigated and their regeneration was also proposed.